Re-voting Processes in Regional Elections: Proses Pemungutan Suara Ulang Pilkada Kabupaten Bungo 2025 - Susi Susanti; Usni Usni (Indonesian Journal of Law and Economics Review, 2026)
General Background: Regional elections serve as a vital instrument of local democracy and a manifestation of popular sovereignty in Indonesia, governed by principles of direct, general, free, secret, honest, and fair conduct. Specific Background: Despite established legal frameworks, administrative and procedural irregularities in the 2025 Bungo Regency Regional Election led to the Constitutional Court mandating a re-voting process (PSU) across several polling stations. Knowledge Gap: While the mechanics of elections are well-documented, there is limited analysis regarding the social-political dynamics, community trust, and specific implementation challenges inherent in localized PSU processes. Aims: This study aimed to analyze the implementation of the PSU in the 2025 Bungo Regency Regional Election, examining obstacles, oversight mechanisms, and levels of community participation. Results: The findings indicate that while the PSU was conducted according to regulatory requirements, it faced significant technical and social challenges, including logistical issues and implementation readiness. Furthermore, voter participation declined compared to the initial election, reflecting public political fatigue and waning trust. Novelty: This study provides a comprehensive evaluation of PSU as a corrective constitutional mechanism that tests the resilience of local democracy and the professional integrity of electoral organizers. Implications: To safeguard future democratic quality, it is essential to bolster the capacity of election organizers, strengthen voter education initiatives, and optimize independent oversight of political actors to restore and maintain public legitimacy. Highlights The Constitutional Court-mandated re-voting process serves as a critical corrective measure for addressing procedural integrity failures and maintaining constitutional democracy. Voter participation rates showed a marked decline following the implementation of re-voting, underscoring a deepening crisis of public trust in localized electoral processes. Structural challenges in electoral management, such as logistical inadequacies and inconsistent adherence to voter identification procedures, remain primary obstacles to successful election administration. Keywords: Re-vote; 2025 Bungo Pilkada; Political Participation; Election Implementation; Election Result Dispute